Study of the morphology of organic ferroelectric diodes with combined scanning force and scanning transmission X-ray microscopy - Bernard, Laetitia; Khikhlovskyi, Vsevolod; Breemen, Albert J. J. M. van; Michels, Jasper J.; Janssen, René A. J.; Kemerink, Martijn; Gelinck, Gerwin; Pilet, Nicolas (Organic electronics, 2018)
Organic ferroelectric diodes attract increasing interest as they combine non-destructive data read-out and low cost fabrication, two requirements in the development of novel non-volatile memory elements. The macroscopic electrical characteristics and performances of such devices strongly depend on their structural properties. Various studies of their global microscopic morphology have already been reported. Here, a multi-technique approach including different scanning force and X-ray microscopies permitted to reveal and locally study nanometer-scale unexpected sub-structures within a P(VDF-TrFE):F8BT ferroelectric diode. The strong impact of these structures on the local polarizability of the ferroelectric is shown. Two alternative fabrication methods are proposed that prevent the formation of these structures and demonstrate improved macroscopic device performances such as endurance and ON/OFF ratio.